Accounting of fixed assets in conditions of sustainable development - Grechenko, R. I. (National Aviation University, 2020)
Effective use of fixed assets necessitates the introduction of a scientifically system of fixed assets accounting at the enterprise that meets management requirements. Market relations determine the objective need to increase the role of accounting in enterprise management. In the new environment, the need for more efficient use of accounting to control and improve their work is increasing
Keywords: accounting to control; market relations; accounting standard